2022
DOI: 10.3390/foods11213347
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Neural Network Assisted Multiobjective Optimization of Postharvest Blanching and Drying of Blueberries

Abstract: This study aimed to optimize the postharvest blanching and drying process of blueberries using high-humidity air impingement (HHAIB) and hot-air-assisted infrared (HAIR) heating. A novel pilot-scale hot-air-assisted carbon-fiber infrared (IR) blanching/drying system was developed. Fresh blueberries with an average diameter of 10~15 mm were first blanched with high-humidity air at 110 °C and 12 m/s velocity for different durations (30, 60, 90, and 120 s); subsequently, the preblanched blueberries were dried at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…This result was obtained because the drying rate decreased substantially at the last stage of drying, resulting in a large increase in drying time [40]. The energy consumption of equipment was directly related to the length of drying time, so SEC decreased rapidly with increasing moisture content [20]. Among the three drying parameters, moisture content had the greatest influence on drying time and SEC.…”
Section: Drying Time and Specific Energy Consumptionmentioning
confidence: 97%
See 1 more Smart Citation
“…This result was obtained because the drying rate decreased substantially at the last stage of drying, resulting in a large increase in drying time [40]. The energy consumption of equipment was directly related to the length of drying time, so SEC decreased rapidly with increasing moisture content [20]. Among the three drying parameters, moisture content had the greatest influence on drying time and SEC.…”
Section: Drying Time and Specific Energy Consumptionmentioning
confidence: 97%
“…The major goal of MOO is to find the Pareto front [19]. Obtaining the global optimal solution in the Pareto front in accordance with the specific optimization purpose is easy [20].…”
Section: Introductionmentioning
confidence: 99%
“…Fabani et al [33] demonstrated that, in convective drying experiments, GA-BPNN can better represent the drying kinetics of watermelon peels compared to 11 different empirical models. Yang et al [34] optimized an artificial neural network using GA to effectively predict and optimize the drying time and energy consumption during the drying-assisted walnut cracking process. Raj et al [35] employed GA to optimize an ANN for modeling and analyzing the microwave vacuum drying of dragon fruit slices.…”
Section: Introductionmentioning
confidence: 99%
“…Recent developments in the branch of food drying involve advancements in the development of mathematical models [1,2], spanning empirical, semi-empirical, and theoretical approaches [3,4]. Researchers have increasingly employed computational methods, including artificial neural networks [5,6], convolutional networks [7][8][9], random forests [10,11], support vector machines [12,13], and more, to analyze the impacts of diverse drying conditions and methods on food quality and safety.…”
Section: Introductionmentioning
confidence: 99%